A biological study of supernumerary teeth derived dental pulp stem cells based on RNA‐seq analysis. (20th January 2019) - Lu, X.; Liu, S‐F.; Wang, H‐H.; Yu, F.; Liu, J‐J.; Zhao, Y‐M.; Zhao, S‐L.
Abstract: Aim: To identify the basic characteristics and gene expression profiles of supernumerary teeth derived stem cells (SNTSCs) and compare them with those of normal dental pulp stem cells (DPSCs). Methodology: Flow cytometry was conducted to identify the protein expression of stem cell markers. Cell proliferation, migration and differentiation abilities of both SNTSCs and DPSCs were determined by CCK8, transwell and differentiation assays, respectively. Gene expression profiles were studied by RNA sequencing analyses. After knocking down the expression of certain differential expression genes (DEGs), the function of DEGs was investigated by CCK8 and transwell assays. Statistical differences were determined using a two‐tailed t ‐test and P values below 0.05 were considered significant. Results: Supernumerary teeth derived stem cells were capable of differentiating into adipocyte, chondrocyte and osteoblast lineage cells, and compared to ordinary DPSCs, SNTSCs had a significantly higher cell proliferation rate ( P < 0.01) and significantly lower migration rate ( P < 0.01). RNA‐seq results revealed the differential expression genes (DEGs) between SNTSCs and DPSCs. A principal component analysis (PCA) and cluster analysis revealed that the gene expression patterns of SNTSCs and DPSCs were different from each other. A total of 12 861 genes were differentially expressed at a significant P value ( P ≤ 0.01), and 5292 of these increased in SNTSCs and 7569 decreased. Further study on the selected DEGs revealed that FUT11, FAM155A and BRD2 inhibited the cell proliferation rate of SNTSCs, and FUT11 and GLUD1 inhibited the cell migration rate, whilst FAM155A promoted the migration rate. Conclusions: The biological characteristics and gene expression profile of SNTSCs was revealed. The stem cell properties of SNTSCs were similar to normal DPSCs but they had a high cell proliferation rate and may have greater potential for cell differentiation.